2013
DOI: 10.1016/j.ygcen.2012.12.013
|View full text |Cite
|
Sign up to set email alerts
|

Corticosterone metabolism by chicken follicle cells does not affect ovarian reproductive hormone synthesis in vitro

Abstract: Highlights► Chicken follicle cells degrade corticosterone to mostly 20β-dihydrocorticosterone in vitro. ► Corticosterone did not affect enzymatic conversion of progesterone and DHEA by ovarian tissue. ► Metabolites such as 17α-hydroxyprogesterone, androstenedione and testosterone were formed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 56 publications
1
7
0
Order By: Relevance
“…At the age of 23 days, chickens showed two factors. One included HDL and 17-OHP, the other one comprises progesterone and cortisol (see Table 2), which agrees with the data of S. Rettenbacher et al [29]. These authors showed that an increase in the glucocorticoid content due to stress or exogenous experimental impact (for example, glucocorticoid administration to intact chickens) can lead to a decrease in the conversion of progesterone to 17-OHP and its derivatives due to inhibition of specific enzymes (e.g.…”
Section: Factor Analysis With Principal Component Methods Of Blood Biosupporting
confidence: 88%
See 2 more Smart Citations
“…At the age of 23 days, chickens showed two factors. One included HDL and 17-OHP, the other one comprises progesterone and cortisol (see Table 2), which agrees with the data of S. Rettenbacher et al [29]. These authors showed that an increase in the glucocorticoid content due to stress or exogenous experimental impact (for example, glucocorticoid administration to intact chickens) can lead to a decrease in the conversion of progesterone to 17-OHP and its derivatives due to inhibition of specific enzymes (e.g.…”
Section: Factor Analysis With Principal Component Methods Of Blood Biosupporting
confidence: 88%
“…At the same time, in incubated in vitro ovarian tissues of female chickens and testicles of males (i.e. without exogenous stress impact), glucocorticoids do not interfere with the progesterone transformation into 17-OHP and then into androstenedione, testosterone and other steroid products [29]. It was shown [30] that stress inhibits the enzyme responsible for the conversion of cholesterol to pregnenolone.…”
Section: Factor Analysis With Principal Component Methods Of Blood Biomentioning
confidence: 98%
See 1 more Smart Citation
“…Though this determination is outside the scope of the present study, we outline two nonmutually exclusive hypotheses to help direct future research. First, females could reduce the accumulation of circulating plasma corticosterone in yolks during vitellogenesis through catalysis at follicles via enzymes such as 11β-HSD (Rettenbacher et al, 2013;Yang, 1997). Second, during vitellogensis and nesting, females may have a hypo-reactive HPA axis (Jessop et al, 2000, Jessop, 2001Paitz et al, 2014;Valverde et al, 1999), reducing the amount of circulating steroid available for accumulation in the yolk.…”
Section: Discussionmentioning
confidence: 99%
“…We extracted steroids from egg yolk according to Rettenbacher, Henriksen, Groothuids, and Lepschy (2013). Briefly, we homogenized three egg yolks, and 5 g was mixed with 10 mL of double-distilled water and stirred for 30 min.…”
Section: High-performance Liquid Chromatography Analysismentioning
confidence: 99%